Book Review of Sidney Sheldon’s Nothing Lasts Forever Written by Sidney Sheldon - Verdiana, Mutia (LANTERN (Journal on English Language, Culture and Literature), 2015)
Discrimination is often found in society, it is caused by the human being inclination to discriminate the others. Discrimination is treating people differently, in which this treatment is made based on the characteristic which has been represented by the people like race, nation, gender, and more. Women sometimes become an object of discrimination because many people underestimate women, especially women who work in particular job.